A Systematic Review of the Evidence Base for Active Supervision in Pre-K–12 Settings. (May 2020) - Allen, Grant Edmund; Common, Eric Alan; Germer, Kathryn A.; Lane, Kathleen Lynne; Buckman, Mark Matthew; Oakes, Wendy Peia; Menzies, Holly Mariah
Active supervision is a proactive, low-intensity strategy to minimize challenging behaviors and increase desired behaviors. To examine the evidence base of this strategy, we applied the Council for Exceptional Children's (CEC) Standards for Evidence-Based Practices in Special Education to the body of research exploring the impact of active supervision with Pre-K–12 students in traditional school settings. In this systematic literature review, we identified seven peer-reviewed, single-case design, treatment-outcome studies meeting inclusion criteria. All studies met a ≥80% weighted criterion of CEC's quality indicators. These seven studies included 15 cases aggregated at the school, classroom, or grade level, collectively involving 1, 686 participants. Three studies included three or more cases and demonstrated positive effects across primary dependent variables (with one study showing neutral effects on a secondary dependent variable). Based on available evidence and using CEC criteria, we determined active supervision to be a potentially evidence-based practice . We discuss implications, limitations, and future directions.